2021
DOI: 10.3390/plants10061174
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Prediction across Structured Hybrid Populations and Environments in Maize

Abstract: Genomic prediction (GP) across different populations and environments should be enhanced to increase the efficiency of crop breeding. In this study, four populations were constructed and genotyped with DNA chips containing 55,000 SNPs. These populations were testcrossed to a common tester, generating four hybrid populations. Yields of the four hybrid populations were evaluated in three environments. We demonstrated by using real data that the prediction accuracies of GP across structured hybrid populations wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 39 publications
1
3
0
Order By: Relevance
“…This is in line with previous findings that showed that adding less related lines to a training set did not reduce the predictive ability (e.g. Brauner et al 2020 ; Li et al 2021 ; Zhu et al 2021 ) and increasing the training set size generally results in higher predictive abilities of genomic selection (e.g. Zhao et al 2012 ; Thorwarth et al 2017 ; Li et al 2021 ; Zhu et al 2021 ).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…This is in line with previous findings that showed that adding less related lines to a training set did not reduce the predictive ability (e.g. Brauner et al 2020 ; Li et al 2021 ; Zhu et al 2021 ) and increasing the training set size generally results in higher predictive abilities of genomic selection (e.g. Zhao et al 2012 ; Thorwarth et al 2017 ; Li et al 2021 ; Zhu et al 2021 ).…”
Section: Discussionsupporting
confidence: 92%
“…5 ). Genomic prediction has been described to strongly depend on the relatedness between training and prediction set ( Albrecht et al 2011 ; Riedelsheimer et al 2013 ; Li et al 2021 ; Zhu et al 2021 ). Our results corroborate these findings, as the prediction among groups resulted in only low predictive abilities, even for the predictions among the more closely related Flint material.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is possible that GS by itself will be better than conventional programs in cases with even higher levels of G×E interaction, or cases where the genomic models are more accurate. Many different approaches to improve prediction accuracy have been previously shown, such as including non‐additive effects in the model (Dias et al., 2018; Oliveira et al., 2020; Zystro et al., 2021b), the relationship between the individuals from the training population and the target population (Li et al., 2021), among others. In addition to these considerations, our work highlights the impact that cycle time can have in a GS program.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that GS by itself will be better than conventional programs in cases with even higher levels of G×E interaction, or cases where the genomic models are more accurate. Many different approaches to improve prediction accuracy have been previously shown, such as including non-additive effects in the model (Dias et al, 2018;, the relationship inbetween the individuals from the training population and the target population (Li et al, 2021), among others.…”
Section: Discussionmentioning
confidence: 99%